The Role Of The International Monetary Fund In Resolving Venezuela's Economic Crisis During Covid-19 - Munzilin, Khairul; Wijaya, Bagaskara Sagita; Nurfajri Fasa, Muhammad Ziddane (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
Venezuela's financial crisis is causing significant suffering to its people. The presence of the COVID-19 pandemic has made Venezuela's list even heavier. The IMF is known as an international financial organization that is often involved in handling financial crises in several affected countries. However, the IMF's involvement in handling the financial crisis and health crisis at the same time was the first experience for the IMF. This research is necessary because it seeks to reveal the IMF's involvement in Venezuela's financial crisis during COVID-19 and makes this the first experience for the IMF in efforts to resolve a country's financial crisis during the COVID-19 pandemic. This research discusses the role of the IMF in resolving Venezuela's economic crisis during the COVID-19 pandemic. This research uses the concepts of foreign aid and economic liberalization with descriptive qualitative research methods and data collection techniques from various documents, books, archives, journals, and theses. This research shows that the IMF has a significant role in resolving Venezuela's economic crisis during the COVID-19 pandemic, including by providing loans, advice and training in crisis management, which can help Venezuela improve its economy and implement economic liberalization in order to pursue Venezuela's economic system more open for the development of economy.Â Keywords: IMF, Venezuela, Economic Crisis, Foreign Aid, Economic Liberalization